Formulação da estratégia em um hospital privado geral e de grande porte na cidade de São Paulo: estudo de caso - Barbanti, Lauro Ferreira (2000)
The formulation of the strategy was studied in a private, general and large hospital in the city of São Paulo, trying to establish the way the strategy is formulated and implemented, related to some current business views. The process of strategic formulation observed can be compared to the new concepts used for the uncertainty levei of the Heath Market in Brazil. In this environment, the hospital strategy also meant to observe the tendencies in other countries, since the position of this organization puts it in a more uncertainty levei, because there are no models to be followed. The strategic formulation, though, ends up using other than just numbers to decide what options should be taken, since the future of its projects is still unknown. Even though, this hospital may be better assisted with a higher degree of structured tools, what it has been currently doing, getting certifications from international organizations and implementing an integrated information's system. This should not make them forget the intuition and creativity which is present in the current process.